1999
DOI: 10.3171/foc.1999.6.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for acute spinal cord injury study pilot study #2: evaluation of protocol for decompressive surgery within 8 hours of injury

Abstract: Acute spinal cord injury (SCI) is a major public health problem for which there is still only limited treatment available. The National Acute Spinal Cord Injury Study-2 (NASCIS-2) and -3 clinical trials demonstrated that the use of acute pharmacotherapy with methylprednisolone can attenuate the secondary injury cascade if administered within 8 hours of acute SCI. However, no trial has been performed to examine whether acute surgical decompressive procedures within this critical 8-hour time window can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 25 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…Nevertheless the indication, the timing and even the role of this intervention in improving neurological recovery remains controversial because of the lack of unequivocal evidence. 10,37,42 The objective difficulties in designing and conducting large prospective randomized studies and, at the same time, the urgent necessity to clarify the role of surgery has spurred a reanalysis of the enormous quantity of data produced in the past decades regarding SCI. Fehlings et al 37 recently reviewed the literature using the modern criteria of evidence-based medicine and arrived to a qualitative evaluation of the available data, concluding that there are Class III data suggesting a role for urgent decompression in the setting of bilateral facet dislocation, and in incomplete injuries in patients with neurological deterioration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless the indication, the timing and even the role of this intervention in improving neurological recovery remains controversial because of the lack of unequivocal evidence. 10,37,42 The objective difficulties in designing and conducting large prospective randomized studies and, at the same time, the urgent necessity to clarify the role of surgery has spurred a reanalysis of the enormous quantity of data produced in the past decades regarding SCI. Fehlings et al 37 recently reviewed the literature using the modern criteria of evidence-based medicine and arrived to a qualitative evaluation of the available data, concluding that there are Class III data suggesting a role for urgent decompression in the setting of bilateral facet dislocation, and in incomplete injuries in patients with neurological deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…32,34,[40][41][42][43][44][45] Most studies reported on retrospective case series with historical controls (Class III evidence).…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of neurologic outcome, the field of SCI research is torn between substantive evidence from preclinical animal models favoring early surgery [29,31,48] and mixed evidence from human clinical trials. Recent preliminary results from the Surgical Treatment for Acute Spinal Cord Injury Study (STASCIS) suggest decompression of the spinal cord within 24 hours of injury is associated with improved neurologic recovery in persons with cervical injury [45]. A final report from this multicenter prospective cohort study is expected within the next year after longterm followup is complete.…”
Section: Discussionmentioning
confidence: 99%
“…There are 8 prospective nonrandomized case series (class 2 evidence) (23,25,(31)(32)(33)(51)(52)(53) and several retrospective case series with historical controls (class 3 evidence) that have addressed the role of spinal cord decompression. None has shown an advantage to surgery in the setting of a complete SCI.…”
Section: Discussionmentioning
confidence: 99%